Association of Saturation of Body Mass Index and Lumbar Bone Mineral Density for Adults - Humaira Sami Ullah, Amber Naureen, Muhammad Afzal, Huma Saeed Khan, Aamir Nazir, Syed Soban Ahmed Tirimzi (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Body mass index has affect on the bone mineral density. However, a very high body mass index has been shown to be detrimental to health. But there is a gap in studies about exactly how much body mass index is most beneficial for bone mineral density. The present study aims to bridge this gap by analyzing data on body mass index saturation and its effects on lumbar bone mineral density in mid-aged adults. Objectives: To ascertain whether there is a body mass index saturation value that existed, to maintain optimal bone mineral density and to find the association of saturation of body mass index and lumbar bone mineral density for adults. Study design: Cross-sectional analytical study. Place and duration of study: Medical Unit 2, Bolan Medical Complex Quetta from 1st April 2013 to 30th April 2020. Methodology: Ninety cases were selected, comprising of 30 each of pre-menopausal women, menopausal women and men. The enrolled cases were within the age of 40-65 years. The anthropometric measurement of body mass index was performed through the digital measuring device for weight in kilograms and height in centimeters. A central DEXA scan for lumbar spine and total hip was conducted using dual energy x-ray absorptiometry. Bone mass density was measured through T scoring technique. A well-structured questionnaire was adapted for entering the demographic, clinical and body mass index and bone mineral density association. Results: The mean age of the premenopausal women was 39.8±4.4 years, while menopausal and men enrolled had a mean age of 59.8±4.5 and 52.3±4.4 years respectively. The mean body mass index of the men and the premenopausal women was in the overweight (28.5±1.4 and 27.4±2.3) category respectively while of the menopausal women it was in the obese category with 33.1±5.1 kg/m2 weight. There was significant variance in the lumbar and spine bone mineral density, premenopausal and men as highest and, menopausal as lowest. The association analysis between the body mass index and bone mineral density showed that the individuals having increased body mass index above 27 kg/m2 had low T score, so that the bone mineral density was turned to a T score which showed osteoporosis in many cases, especially in menopausal group. The linear regression analysis values showed that there was a high significant association of menopausal women weight with the lumbar spine and total hip bone mineral density. The similar significance was observed in the pre-menopausal women as well as men. Conclusion: There is a strong association between body mass index and bone mineral density of the individuals. The bone mineral density increases with the increase in body mass index, until a saturation level of 27 kg/m2, beyond which the bone mineral density reduced. Keywords: Association, Saturation, Bone mineral density, Body mass index, Lumbar bone